Effects of tualang honey supplementation on oxidative stress status, inflammation and lipid profiles in chronic smokers - Wan Ghazali, Wan Syaheedah (2014)
Elevated oxidative stress, inflammation and alteration in lipid profiles in smokers have been proposed as among the major factors that contribute to the development of smoking-related cardiovascular disease. However, the possible beneficial effect of Tualang honey that has antioxidant, anti-inflammatory and antilipid properties among smokers has yet been reported. The aims of this study, therefore, to determine the effects of Tualang Honey supplementation on oxidative stress markers, inflammatory markers and lipid profiles in smokers. A total of 36 non smokers and 72 smokers were recruited. The smokers were then randomly divided into 2 groups namely smokers without supplementation and smokers with honey supplementation at the dose of 20 gram/day for 12 weeks. Blood was obtained for determination of oxidative stress markers, inflammatory markers and lipid profiles from all groups at pre-intervention and from smokers group at post-intervention. At pre-intervention, smokers had significantly higher levels of F2-isoprostanes, total antioxidant status (TAS) and catalase (CAT) activity compared to non smokers. Meanwhile, the activities of superoxide dismutase (SOD) and glutathione peroxidase (GPx) were significantly lower in smokers than non smokers. A significantly higher level of high sensitivity C-reactive protein (hsCRP) was found in smokers compared to non smokers. However, no significant differences were found for the levels of tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6). Furthermore, significantly lower high-density lipoprotein (HDL) as well as higher total cholesterol (TC), low-density lipoprotein (LDL) and triglyceride (TG) levels were observed in smokers compared to non smokers. In smokers, Tualang honey supplementation significantly decreased the level of F2-isoprostanes as well as increased the levels/activities of TAS, CAT and GPx. Tualang honey also significantly increased the level of TNF-α and decreased the level of hsCRP. Apart from that, Tualang honey significantly decreased the levels of TC and LDL. These observations might suggest a beneficial effect of Tualang honey against cigarette smoke-induced oxidative stress, inflammation as well as alteration in lipid profiles among smokers which may provide an effect in reducing the atherothrombosis formation and subsequent risk of cardiovascular disease. These beneficial effects could be, partly attributed to its various components which include phenolic acids and flavonoid compounds that have antioxidant, anti-inflammatory and antilipid properties. However, further studies are required to elucidate the exact mechanism of action on these benefical effects of Tualang honey